The role of social responsibility practices in enhancing the quality of work life (With reference to the experience of Google Company) - Mabrouki, Fateh; Youcefi, Alaeddine; Ziouche, Said; Ounnoughi, Nabil (The International tax journal, 2025)
This study aimed to highlight the role played by social responsibility practices in all their dimensions in improving the quality of work life. The research addressed the theoretical framework of both social responsibility and quality of work life by presenting the concept and importance of these two variables, in addition to highlighting the relationship between social responsibility and quality of work life. The study showed that companies focusing on social responsibility enjoy a good reputation, which contributes to achieving outstanding performance that positively reflects on employees' lives, illustrated through Google's experience in applying social responsibility practices.